2022
DOI: 10.2147/jpr.s351576
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Moxibustion Smoke for Stage 1 Post-Stroke Shoulder-Hand Syndrome: Protocol for a Multi-Center, Single-Blind Randomized Sham-Controlled Trial

Abstract: Objective This study aims to evaluate the safety and efficacy of various levels of moxibustion smoke concentration (MSC), represented by particulate matter 10mm (PM 10 ), on pain and motor dysfunction in patients with stage 1 post-stroke shoulder-hand syndrome (SHS). Materials and Methods In this multi-center, sham-controlled, single-blind, randomized controlled trial (RCT), a total of 140 eligible patients with stage 1 post-stroke SHS will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Previous studies have shown [19] that CGRP is a neuropeptide belonging to the calcitonin gene-related peptide family, which is highly expressed in peripheral sensory nerves and the central nervous system, and is involved in the transmission of nociceptive information and the formation of pain sensitization in the periphery and the spinal cord, and interacts with biologically active substances or receptors such as substance P in the process of pain modulation, which has a strong vasodilatory effect. Some studies have shown [20] that the change of CGRP level is related to the severity of nerve damage after hemorrhagic stroke, and it is also an important indicator for evaluating the prognosis of hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown [19] that CGRP is a neuropeptide belonging to the calcitonin gene-related peptide family, which is highly expressed in peripheral sensory nerves and the central nervous system, and is involved in the transmission of nociceptive information and the formation of pain sensitization in the periphery and the spinal cord, and interacts with biologically active substances or receptors such as substance P in the process of pain modulation, which has a strong vasodilatory effect. Some studies have shown [20] that the change of CGRP level is related to the severity of nerve damage after hemorrhagic stroke, and it is also an important indicator for evaluating the prognosis of hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent article “Efficacy of Moxibustion Smoke for Stage 1 Post-Stroke Shoulder-Hand Syndrome: Protocol for a Multi-Center, Single-Blind Randomized Sham-Controlled Trial” 1 published by Xiaonan Meng et al in the Journal of Pain Research. By reading this article attentively, I would like to share some thoughts and personal understanding to this article.…”
Section: Dear Editormentioning
confidence: 99%
“…In the high MSC group, all four devices will each contain one lit stick of conventional moxa. Each moxibustion treatment will last for 20 minutes per session, with 5 weekly sessions being conducted over the course of 6 weeks [413] ① Based on the 2018 Chinese guideline for the diagnosis and treatment of rheumatoid arthritis, patients in both groups will be administered 12.5 mg methotrexate once per week (2.5 mg/pill, 030170202, SPH Sine Pharmaceutical Laboratories Co., Ltd, Shanghai, China). An additional 2.5 mg of methotrexate will be administered if patients experience uncontrolled pain, swelling or stiffness.…”
Section: Q8mentioning
confidence: 99%